Pharmacokinetics and brain penetration study of chlorogenic acid in rats - Kumar G.; Paliwal P.; Mukherjee S.; Patnaik N.; Krishnamurthy S.; Patnaik R. (My University, 2025)
1. The present study is designed to investigate the brain distribution and plasma pharmacokinetics profiles of chlorogenic acid (CGA) after intranasal administration in Charles–Foster rats to evaluate whether the CGA molecules are transported directly via the nose-to-brain path. 2. The CGA is administered intravenously (IV) and intranasally (IN) at the dose of 10 mg/kg. Further, its concentration in the plasma, cerebrospinal fluid (CSF) and the whole brain is analyzed by HPLC-UV method. 3. The study observes that CGA is rapidly absorbed in plasma with t max of 1 min similar to IV route after IN administration. The peak plasma concentration and AUC 0–24 are higher by 3.5 and 4.0 times respectively in IV administration, compared to IN delivery that represents the significant less systemic exposure of CGA in IN route. 4. However, the concentration of CGA in the brain is 4, 6.5, 5.3, 5.2 and 4.5 times higher at 30, 60, 120, 240 and 360 min, respectively in IN administration compared to IV administration. The exposure of CGA in the brain after IN administration (AUC brain, IN ) was significantly greater (4 times) as compared to the exposure of CGA in the brain (AUC brain, IV ) after IV administration reflecting significant brain uptake of CGA through nasal route. Therefore, IN delivery of CGA can be a promising approach for the treatment of stroke and neurodegenerative disorders. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.